PENGUJIAN KINERJA PEMBANGKIT LISTRIK TENAGA SURYA - djamin, martin (Badan Pengkajian dan Penerapan Teknologi, 2012)
In order to investigate the behavior of the solar home systems, 10 data loggers have been installed in three different villages in Kolaka district in Southeast Sulawesi in March 2001. The solar home systems installed in Kolaka consists of a 50 Wp Solarex MSX 50 modules, 70 Ah battery, 10A/12volt battery charge regulator (BCR) and three 6W fluorescent lights. This paper will present and elaborate the performance of solar home systems, which includes Vbattery, VLoad, ILoad, Imodule and comparison between theoretical calculation and field measurement. Results of monitoring nine solar home systems in Kolaka district in Indonesia are presented. Data logger information shows typical load patterns, and differences between users. The information allows for break-down of a number of different energy loss categories. Some of these losses can be reduced by the user.